Analysis of Criminal Law Sanctions' Application Against Statutory Rape from the Positive Law Perspective on Ambon Island and Lease Islands - Rahawarin, Fauzia; Nursalam, Nursalam (Technium Social Sciences Journal, 2021)
The purpose of this study was to analyze the application of criminal law sanctions against statutory rape in Indonesia. The analysis employed a positive law perspective and an empirical legal approach. The research data consisted of verbal utterances and observation results collected from Criminal Investigators at the Ambon Island and Lease Islands’ police stations. Data analysis was carried out through (1) data reduction, (2) data display, and (3) conclusion. The results of this study indicate that criminal sanctions against statutory rape in Indonesia are applied through the process of investigation, visum et repertum, prosecution and summons of suspects and witnesses, statements of criminal penalties for the perpetrators, and prevention of sexual immorality and rape. The criminal sanctions are based on “Law Number 35 of 2014 about Amendments to Law Number 23 of 2002 concerning Child Protection Articles 76D and 81. Keywords: criminal, intercourse, positive law